Community Empowerment Through Social Service: The Role of Sacrificial Animal Slaughter in Strengthening Solidarity and Economic Resilience in Sidoharjo Village, Pulung Ponorogo - Syahrudin ,; Isa, Khairunesa; Susanto, Roni (Journal of Social Transformation and Regional Development, 2025)
The slaughter of sacrificial animals (qurban) is a religious practice in Islam that carries profound spiritual significance alongside its broad social and economic dimensions. This study aims to analyze the implementation of social service activities through qurban slaughter in Sidoharjo Village, Pulung, Ponorogo, and its impact on strengthening social solidarity and empowering the local economy. Using a qualitative approach with a case study method, the research involved direct observation during the activity, in-depth interviews with organizers, community leaders, and beneficiaries, as well as documentation analysis. The findings reveal three key impacts of qurban activities in Sidoharjo Village. First, in the social aspect, the activity fosters community solidarity through active participation in all stages, from fundraising and animal slaughter to meat distribution. Second, the meat distribution contributes significantly to food equity, particularly for underprivileged groups who have limited access to protein sources. Third, the activity positively impacts the local economy, benefiting livestock farmers who experience increased demand for sacrificial animals. Moreover, community involvement in managing the event creates temporary economic opportunities, such as roles in logistics and slaughter operations. This study highlights the importance of qurban slaughter as a community service model that integrates religious values with social harmony and economic empowerment. The findings provide valuable insights for implementing similar programs in other communities, emphasizing structured management to maximize their impact.